eq#1) -1/r(d/dr)(r*tao)=0 eq#2)tao=m(-dv/dr)^n (n is a parameter) for v=0 at r=R and v=V and r=kR (k and V are parameters) I have no idea how to start this or what is the correct way to start. I initially integrated tao to get dtao/dr=m(-dv/dr)^n-1, but this just complicates things further with the n-1. Next i plugged in tao into the first equation and then used the product rule so -1/r(d/dr)(r*m(-dv/dr)^n)=0 once again i get the n-1 factor. Then i tried taking the derivative of #1 with respect to r to yield -(1*tao)/r=0. Please could someone please guide me in the right steps!!!